Prototyping of a two-wheeled mobile robot for sustainable manufacturing development based on triangulation method and software development - Hamdan Mohammad; Kamal Israa Wahbi; Abu-Jassar Amer; Maksymova, S.; Lyashenko, V. (My University, 2025)
This article presents a mobile robot prototyping and software development for its control production. A created robot prototype moves using a two-wheeled base and is equipped with ultrasonic sensors. This design allows increasing the maneuverability of the robot and reducing the turning radius. The specific arrangement of the sensors allows expanding the area of obstacle detection. The developed software includes receiving data from the sensors, processing them and constructing a movement trajectory in accordance with the target and the current environment state. The trajectory is constructed using the triangulation method. This allows accurately determining the distance to the obstacle, constructing a rational movement trajectory and going around obstacles that may arise on the path of the robot. A number of experiments were conducted that allow us to say that the obstacle detection range is sufficient for a timely response and change the trajectory of movement.
Keywords: Mobile Robot; Triangulation